Sociodemographic Determinants of Nonattendance in a Population-Based Mammography Screening Program in the City of Manisa, Turkey - Pınar Erbay Dundar; Beyhan Cengiz Ozyurt; Koray Erdurak (The Scientific World Journal)
Objectives. Community based breast cancer screening has decreased breast cancer mortality in women. This study examined the predictors of nonattendence for invitational breast cancer screening in relation to socioeconomic status in the city of Manisa, in western Turkey. Study Design. For the evaluation of the reasons for refusing to participate in the study, two districts were selected. 446 women aged between 50 and 69 years were selected from the program database by systematic random sampling. Methods. The questionnaire consisted of sociodemographic variables and the adapted version of Champion's Health Belief Model Scale. Univariete and multivariete logistic regression analysis were performed throughout the data analysis. Results. Being from an urban district and being from the western region were the risk factors for not participating in the screening program (𝑃=0.014, 𝑃=0.023). A statistical significance was found between mammography-benefit, mammography-barrier and program participation (𝑃=0.044, 𝑃=0.006). Although there were many more barriers for not participating in the screening program for the women of the slum district, the attendence rate of the slum district was higher than that of the urban district. Conclusions. Increased attendance may be achieved through enhancement of breast cancer awareness and by reducing some of the modifiable barriers.